NUSHŪZ SUAMI-ISTRI DAN SOLUSINYA: Studi Tafsīr al-Rāzī - Fatimah Zuhrah (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2016)
Nushūz means a wife do anything against her husband for no reason that can be accepted by Islamic law (wife nushūz), or husband does not carry out its obligations as stipulated in Islamic law (husband nushūz). This article intends to analyze the concept of nushūz according to Islamic law in the perspective of Fakhr al-Dīn al- Rāzī in his Qur’anic commentary (tafsīr). It also discussed about the solutions of nushūz according to the Qur’an. Based on the study of sura al-Nisa verse: 34, 35, and 128 that nushūz can be done even by the wife or the husband. When problems of nushūz already potentially shiqāq, it is advisable to appoint a ḥakam (mediator), both from husband’s families and wife's families.Nushūz berarti seorang istri melakukan perbuatan yang menentang suami tanpa alasan yang dapat diterima oleh hukum Islam, atau sebaiknya suami tidak menjalankan kewajibannya sebagaimana ketentuan hukum Islam. Artikel ini bermaksud untuk menganalisis konsep nushūz menurut hukum Islam dalam perspektif Fakhr al-Dīn al-Rāzī dalam kitab tafsirnya. Selain itu juga dibahas tentang bagaimana tawaran solusi nushūz menurut al-Qur’an berdasarkan kajian terhadap surat al-Nisā’ ayat 34, 35, dan 128 bahwa nushūz bisa dilakukan oleh istri maupun suami. Ketika permasalahan nushūzsudah mengkhawatirkan sehingga berpotensi shiqāq, maka dianjurkan untuk mengangkat seorang ḥakam (mediator), baik dari keluarga suami maupun keluarga istri.